Astrocyte DNA damage and response upon acute exposure to ethanol and corticosterone - Reyes-Ábalos, Ana Laura; Álvarez-Zabaleta, Magdalena; Olivera-Bravo, Silvia; Di Tomaso, María Vittoria (Frontiers in Toxicology, 2024)
Introduction: Astrocytes are the glial cells responsible for brain homeostasis, but if injured, they could damage neural cells even deadly. Genetic damage, DNA damage response (DDR), and its downstream cascades are dramatic events poorly studied in astrocytes. Hypothesis and methods: We propose that 1 h of 400 mmol/L ethanol and/or 1 μmol/L corticosterone exposure of cultured hippocampal astrocytes damages DNA, activating the DDR and eliciting functional changes. Immunolabeling against γH2AX (chromatin DNA damage sites), cyclin D1 (cell cycle control), nuclear (base excision repair, BER), and cytoplasmic (anti-inflammatory functions) APE1, ribosomal nucleolus proteins together with GFAP and S100β plus scanning electron microscopy studies of the astrocyte surface were carried out. Results: Data obtained indicate significant DNA damage, immediate cell cycle arrest, and BER activation. Changes in the cytoplasmic signals of cyclin D1 and APE1, nucleolus number, and membrane-attached vesicles strongly suggest a reactivity like astrocyte response without significant morphological changes. Discussion: Obtained results uncover astrocyte genome immediate vulnerability and DDR activation, plus a functional response that might in part, be signaled through extracellular vesicles, evidencing the complex influence that astrocytes may have on the CNS even upon short-term aggressions.